An annotated checklist of the macrodasyidan Gastrotricha from India - Chatterjee, Tapas; Priyalakshmi, Geetha; Todaro, M. Antonio (Zootaxa, 2019)
We present a checklist of the macrodasyidan Gastrotricha fauna of India derived from original articles and comprehensive monographies regarding the Indian Fauna. Taxa and specimens described from India are discussed with special attention to their status, especially those species previously known from distant geographic areas. A total of 43 species have been recorded from 4 States and 2 Union territories. A careful taxonomic assessment indicated that many species are in need of re-description as the reported anatomical traits are not sufficient to grant a modern, robust identification. The situation is particularly poor for two species (Macrodasys indicus Govindankutty & Nair, 1969 and Paradasys lineatus Rao, 1980), which consequently, are considered here to be species inquirendae; moreover, the Indian records of Tetranchyroderma hystrix and T. massiliense reported from Kerala are doubtful and consequently the two species should not be included among the fauna of the Indian region until proper evidence is found. It is necessary to unravel the true identities of many Indian species through a comparison to topotypical material. We recommend that future comparisons between related species and conspecifics from different populations to include molecular sequence data